2019
DOI: 10.1186/s40662-019-0155-0
|View full text |Cite
|
Sign up to set email alerts
|

A cellular and proteomic approach to assess proteins extracted from cryopreserved human amnion in the cultivation of corneal stromal keratocytes for stromal cell therapy

Abstract: Background: Human corneal stromal keratocytes propagated in culture media supplemented with human amnion extract (AME) can correct early corneal haze in an animal model. Clinical application of cultivated keratocytes is limited by infectious disease screening before amnion products can be used in humans. It remains unclear if AME from cryopreserved versus fresh human amnion can support human keratocyte propagation, and which components of the extract promote keratocyte growth. Methods: Three placentas were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 52 publications
0
13
1
Order By: Relevance
“…With our approach, we identified 117 core ECM proteins and 168 matrisome-associated proteins ( Table S5 ). This is a significantly higher number than previous similar reports in which 47 core ECM proteins and 63 matrisome-associated proteins were identified [36] . We hypothesize that the higher number of ECM proteins can likely be attributed to the applied extraction method, that is not only extracting soluble proteins, and to the used instrument.…”
Section: Resultscontrasting
confidence: 56%
See 3 more Smart Citations
“…With our approach, we identified 117 core ECM proteins and 168 matrisome-associated proteins ( Table S5 ). This is a significantly higher number than previous similar reports in which 47 core ECM proteins and 63 matrisome-associated proteins were identified [36] . We hypothesize that the higher number of ECM proteins can likely be attributed to the applied extraction method, that is not only extracting soluble proteins, and to the used instrument.…”
Section: Resultscontrasting
confidence: 56%
“…A study focusing on epithelium-denuded amniotic membrane [40] identified 43 highly abundant proteins by Matrix Assisted Laser Desorption/Ionization (MALDI-TOF). More recent work [36] compared the soluble proteins of fresh and cryopreserved human amniotic membranes by isobaric tagging for relative quantification (iTRAQ) and identified 1949 soluble proteins that were unaltered by cryopreservation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One option is the soluble amnion membrane extract (AME). In vitro stromal keratocyte culture studies have shown that the human amnion matrix and its soluble protein extract reduced TGFβ1 and β2-related signaling (Tseng et al, 1999;Espana et al, 2003;Kawakita et al, 2005;Yam et al, 2015;Fenner et al, 2019). Cultured keratocytes had a minimal transition to fibroblastic phenotypes during early passages, even in the presence of serum.…”
Section: Regenerative Cytokinesmentioning
confidence: 99%